Contrasting Influence of Nitrogen Oxides on the Cloud Condensation Nuclei Activity of Monoterpene‐Derived Secondary Organic Aerosol in Daytime and Nighttime Oxidation. Issue 4 (22nd February 2023) - Zhang, Chenqi; Guo, Yindong; Shen, Hongru; Luo, Hao; Pullinen, Iida; Schmitt, Sebastian H.; Wang, Mingjin; Fuchs, Hendrik; Kiendler‐Scharr, Astrid; Wahner, Andreas; Mentel, Thomas F.; Zhao, Defeng
Abstract: Anthropogenic nitrogen oxides may influence the cloud condensation nuclei (CCN) activity of biogenic secondary organic aerosols (SOA) in both daytime photooxidation and nighttime NO3 oxidation, which has significant implications for the climatic impact of SOA. We investigated the influence of NOx on the CCN activity of monoterpene‐derived SOA in OH oxidation and in NO3 oxidation. In OH oxidation, NOx had little influence on the hygroscopic parameter κ of organic aerosol ( κ Org ), which was attributed to the minor fraction of organic nitrates (ON) in SOA (<24%), resulted from the low branching ratio of RO2  + NO to form ON. In contrast, in NO3 oxidation κ Org was much reduced compared to OH/O3 oxidation due to a dominant fraction of ON. We report κ of MT‐derived ON formed in photo‐oxidation and NO3 oxidation (0.029–0.052) for the first time to our knowledge, which may be used to improve model simulations of CCN concentrations. Plain Language Summary: Anthropogenic nitrogen oxides may influence the cloud formation ability of biogenic secondary organic aerosols (SOA) in both daytime and nighttime, which has implications to understand the climatic impact of SOA. However, the influence remains unclear. We found that for monoterpenes, a major class of precursors of biogenic SOA, NOx had little influence on the cloud formation ability of SOA in the daytime oxidation. In contrast, in the nighttime oxidation of monoterpenes by NO3, an important oxidant formed from NOx at night‐time, SOA had much lower cloud formation ability than that in the photo‐oxidation. The difference was attributed to the different fractions of organic nitrates (ON) in SOA. We also determined the κ of monoterpene‐derived ON for the first time to our knowledge. Key Points: In daytime OH oxidation NOx had little influences on the cloud condensation nuclei (CCN) activity of MT‐SOA In nighttime NO3 oxidation MT‐SOA had much lower CCN activity compared with those formed via OH or O3 oxidation We report the κ of monoterpene‐derived organic nitrates (0.029–0.052) for the first time to our knowledge